Endoscopic Submucosal Dissection Outcomes for Gastroesophageal Tumors in Low Volume Units: A Multicenter Survey - Najib Azmi A.; Khor C.J.L.; Ho K.-Y.; Pittayanon R.; Rerknimitr R.; Ratanachu-Ek T.; Koay D.S.C.; Koh J.C.; Ho S.-H.; Goh K.-L.; Mahadeva S. (Hindawi Publishing Corporation, 2024)
Indexed by Scopus